Sustainable livestock farming practices in Punjab, Pakistan: Insights from demographic analysis and disease prevalence - Rana, Hafiz Amjad Ali; Iftikhar, Muhammad; Nasar, Muhammad Fahim (Journal of Agriculture and Biology, 2023)
This study investigates the socio-economic landscape and disease prevalence among livestock farmers in Punjab, Pakistan, focusing on Muzaffargarh and Rahim Yar Khan districts. A sample of 400 farmers was randomly selected using a multistage sampling technique. The demographic analysis reveals a predominantly middle-aged and older farming population, with small to medium landholdings. Specifically, 43.3% of farmers were categorized as old (>50 years), while 65.0% were small-scale landholders (less than 12.5 acres). Regarding disease recognition, foot and mouth disease and hemorrhagic septicemia emerged as the most recognized diseases, with mean scores of 3.30 and 3.22 respectively, on a scale of 1 to 5. Additionally, ticks were identified as the primary external parasite affecting livestock, with a mean score of 3.19. These findings highlight the urgent need for targeted interventions to address disease management and improve farming practices in the region. Strengthening veterinary services, promoting disease prevention measures, and enhancing access to quality fodder are crucial steps toward ensuring sustainable livestock farming in Punjab, Pakistan.
Keywords: Livestock farming; Punjab; Pakistan; Disease prevalence; Socio-economic analysis